Caso Clínico ARP nº 22: Qual o seu diagnóstico? - Condesso, Daniela (2021)
A 49-year-old woman with history of bicytopenia (anemia and leukopenia) and monoclonal gammopathy (IgG lambda) not fully clarified presents with portal hypertension and splenomegaly of unclear cause. Abdominal computed tomography (CT) and magnetic resonance imaging (MRI) were performed for further investigation.